East Asia Pacific at work employment, enterprise, and well-being - Packard, Truman G. 1972- (World Bank E-Library Archive, 2014)
Country categorization by institutional factors --Implications for policy makers concerned about work --Notes --References --Spotlight 2Past Jobs Strategies in East Asia: Could They Work Today? --What exactly are employment -- or jobs -- strategies? --East Asia's experience with employment strategies --Are these strategies viable for emerging East Asia Pacific countries now? --Note --References --8.Well-being from Work in the Pacific Island Countries --Employment challenges of the small Pacific island countries --Five employment priorities for Pacific island countries --Conclusions --Notes --References --9.A Region at a Crossroads --What should an employment strategy set out to achieve? --Remove biases that hurt working people --Make labor regulation and social protection work for all working people --Take proactive measures to address remaining failures and capture externalities --Why should this approach to crafting employment strategies appeal to governments in East Asia Pacific?